Bacteremia Due to Extended-Spectrum-β-Lactamase-Producing Aeromonas spp. at a Medical Center in Southern Taiwan - Wu, Chi-Jung (American Society for Microbiology, 2011)
Although extended-spectrum-β-lactamase (ESBL)-producing aeromonads have been increasingly reported in recent years, most of them were isolates from case reports or environmental isolates. To investigate the prevalence of ESBL producers among Aeromonas blood isolates and the genes encoding ESBLs, consecutive nonduplicate Aeromonas blood isolates collected at a medical center in southern Taiwan from March 2004 to December 2008 were studied. The ESBL phenotypes were examined by clavulanate combination disk test and the cefepime-clavulanate ESBL Etest. The presence of ESBL-encoding genes, including bla(TEM), bla(PER), bla(CTX-M), and bla(SHV) genes, was evaluated by PCR and sequence analysis. The results showed that 4 (2.6%) of 156 Aeromonas blood isolates, 1 Aeromonas hydrophila isolate and 3 Aeromonas caviae isolates, expressed an ESBL-producing phenotype. The ESBL gene in two A. caviae isolates was bla(PER-3), which was located in both chromosomes and plasmids, as demonstrated by Southern hybridization. Of four patients with ESBL-producing Aeromonas bacteremia, two presented with catheter-related phlebitis and the other two with primary bacteremia. Three patients had been treated with initial noncarbapenem β-lactams for 5 to 10 days, and all survived. In conclusion, ESBL producers exist among Aeromonas blood isolates, and clinical suspicion of ESBL production should be raised in treating infections due to cefotaxime-resistant Aeromonas isolates.